FISCAL POLICY, INFLATION THRESHOLD, AND ECONOMIC GROWTH IN MOROCCO (FOR THE PERIOD 1990-2019) (World Bulletin of Management and Law, 2022)
The economists and, fiscal policy creators, and central bank managers agrees that the initial goal of macroeconomic policies is achieving a high and sustainable economic growth rate while maintaining a low inflation rate. And generally its known that high inflation affects the short and long term economics growth. And recently the relationship between inflation and economic growth has got a special interest and has been the main subject for a lot of Theoretical and experimental studies. this research addresses the relationship between inflation and economic growth in Morocco during the period (1990-2019) using the model the "Khan-Sinhaji" in (2001) to determine the inflation threshold. and the outcome was that the inflation threshold in Morocco was about (4%) this actively demonstrates that inflation rates greater than (4%) may cause damage to economic growth. And one of the most important recommendations that this research recommended is that a controlled inflation rate is necessary to stimulate economic growth, and the fiscal policy works through the money supply tool in controlling the level of inflation in an appropriate manner
Keywords: Fiscal policy; growth; and inflation; a model